Modification of austenitic cast iron (Ni-resist) with high manganese content by using heat treatment - Khairul Muzafar, Ahmad (2017)
Austenitic cast iron broadly used in chemical and power plant, automotive and oil and gas industry. This material offers outstanding properties instability at a moderately high temperature and resistance to corrosion and wear which demanded by the industry. Austenitic microstructure in Ni-resist exists due to the influence of nickel as prime austenitic matrix promoter. However, using nickel as prime alloy addition for the production of Ni-resist Alloy is expensive due to its unstable prices. So, employing manganese as nickel replacement or mixing with for austenitic matrix promoter is an option that may reduce total processing cost. Therefore, the present study aims to explore the possibility to reduce nickel consumption by manganese substitution to generate the austenitic structure of Ni-resist. Furthermore, an investigation on the effect of the properties towards modified Ni-resist (Mn-Ni-resist) before and after heat treatment is appealing. Higher manganese austenitic cast iron with reduced nickel content (Mn-Ni-resist) was produced with manganese content nine wt%, ten wt%, 11 wt% and 12 wt% through Y-block according to ASTM A436 by using a green sand mold. Samples were then annealed at 700ºC, 800 ºC, 900 ºC, and 1000ºC for 3 hours before slowly cooled to room temperature in furnace temperature. The complex relationship between the development of the solidification microstructures and build up of micro-segregation due to increasing Mn wt% in Mn-Ni-resist was obtained by using cooling curve thermal analysis and complemented by microscopic observation and mechanical properties. Experimental describe the characterization of microsegregation in Mn-Ni-resist was made using point counting microanalysis along the microstructure. The result showed that manganese addition and heat treatment affect the microstructure and mechanical properties. Solidification cooling curve decreased, and the morphology of austenite dendrite arm shortened as the Mn wt% increased. Then, the strength reduced and more inferior compared to conventional cast iron. Microstructure observations revealed that Mn-Ni-resist consists of flake graphite embedded in the austenitic matrix and the accumulative of carbide at the frame of the rosette flake graphite and also known as late to freeze region (LTF). Higher annealing temperature on the Mn-Ni-resist has successfully reduced carbide formation and slightly increases tensile strength. The higher annealing temperature shows carbide altered into a smaller size and disperses through the austenitic matrix structure. The size of carbide decreased with increasing annealing temperature as observed in the microstructure. On the other hand, hardness diminished as the annealing temperature increases.